Safety And Efficacy Of Princess® FILLER Lidocaine In The Correction Of Nasolabial Folds - Grablowitz D; Sulovsky M; Höller S; Ivezic-Schoenfeld Z; Chang-Rodriguez S; Prinz M (Dove Medical Press, 2019)
Doris Grablowitz,1 Monika Sulovsky,2 Sonja Höller,3 Zrinka Ivezic-Schoenfeld,3 Souyet Chang-Rodriguez,3 Martin Prinz3 1Medizinisch Ästhetisches Zentrum Wien, Wien 1010, Austria; 2YUVELL® Fine Aesthetics, Wien 1010, Austria; 3Croma-Pharma GmbH, Leobendorf 2100, AustriaCorrespondence: Martin PrinzCroma-Pharma GmbH, Industriezeile 6, Leobendorf 2100, AustriaTel +43 2262 684 68-0Fax +43 2262 684 68-165Email martin.prinz@croma.atPurpose: Nasolabial folds (NLFs) are one of the most noticeable signs of facial aging. NLFs negatively affect self-confidence and social acceptance often leading to a person’s desire to improve their appearance using dermal fillers. The hyaluronic acid injectable gel implant Princess® FILLER Lidocaine (PFL) is a minimally invasive easy to administer the product. In this investigation, we assessed the safety and efficacy of PFL to correct moderate to severe NLFs over a 36-week period.Methods: Adult women and men with moderate to severe NLFs received one injection of PFL to both NLFs. After 2 weeks, a touch-up treatment could be performed, if deemed necessary by the investigator. The change in NLF severity was assessed using the Nasolabial Fold Severity Rating Scale (NFL-SRS) developed by Croma-Pharma and the Global Aesthetic Improvement Scale (GAIS).Results: Out of 60 analyzed subjects, 59 (98.3%) had improved their NLF severity by at least 1 grade on the NFL-SRS at week 4, 58 subjects (96.7%) at weeks 24 and 36. All subjects showed aesthetic improvement (GAIS), at weeks 4 and 24. The investigator judged the aesthetics as very much improved (score of 1) in 45 (75.0%) at week 4, 48 (80.0%) at week 24, and in 39 of 60 subjects, respectively (65.0%) at week 36. Thirty-six weeks post-initial treatment, 56 of 60 subjects (93.3%) were very satisfied or satisfied with the treatment. Adverse device effects (ADEs) were mild or moderate and resolved at latest 25 days post-onset. The most commonly reported ADEs were injection site hematoma and injection site pain.Conclusion: PFL was safe and effective in reducing the severity of NLFs. Most subjects were (very) satisfied with the treatment outcome throughout a 36 weeks investigation period.Keywords: hyaluronic acid, dermal filler, lidocaine hydrochloride, mid to deep dermis, facial wrinkles, injection